(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes strategies aimed at increasing the motivation of students studying English. The types of motivation, the factors affecting it, the role of communicative, socioconstructive, humanistic and differential approaches in the language teaching process and the impact of these approaches on student educational motivation are analyzed, as well as the coverage of effective teaching methods and the impact of modern technologies on motivation.